Numerical Simulation of Low-Pressure Carburizing and Gas Quenching for Pyrowear 53 Steel - Bartosz Iżowski; Artur Wojtyczka; Maciej Motyka (Metals, 2023)
The hardness and phase composition are, among other things, the critical material properties considered in the quality control of aerospace gears made from Pyrowear 53 steel after high-pressure gas quenching. The low availability of data on and applications of such demanding structures justify investigating the choice of the material and the need to improve its manufacturability. In this study, computational finite-element analyses of low-pressure carburizing followed by oil and gas quenching of Pyrowear 53 steel were undertaken, the objective of which was to examine the influence of the process parameters on the materials’ final phase composition and hardness. The material input was prepared using JMatPro. The properties computed by the CALPHAD method were calibrated by the values obtained from physical experiments. The heat transfer coefficient was regarded as an objective variable to be optimized. A 3D model of the Standard Navy C-ring specimen was utilized to predict the phase composition after the high-pressure gas quenching of the steel and the hardness at the final stage. These two parameters are considered good indicators of the actual process parameters and are used in the industry. The results of the simulation, e.g., optimized heat transfer coefficients, cooling curves, and hardness and phase composition, are presented and compared with experimental values. The accuracy of the simulation was validated, and a good correlation of the data was found, which demonstrates the quality of the input data and setup of the numerical procedure. A computational approach to heat treatment processes’ design could contribute to accelerating new procedures’ implementation and lowering the development costs.